Design and Usability Testing of a Novel Internet-Delivered Cognitive Behavioral Therapy (iCBT) Software Platform for Children with Anxiety. - Pera, Maria Carmela; Poli, Caterina; Gnazzo, Martina; Baldini, Valentina; Delsante, Laura; Pacchioni, Marco; Orsini, Mirko; Campana, Beatrice Rita; Diodati, Francesca; Puntoni, Matteo; Maglietta, Giuseppe; Caminiti, Caterina; et al. (Children, 2025)
Background: Anxiety disorders are common in childhood, yet access to cognitive behavioral therapy (CBT) is often limited. Internet-delivered CBT (iCBT) can help overcome these barriers, but evidence in younger children remains scarce. This pilot study describes the development and preliminary evaluation of an Italian iCBT platform for children with mild to moderate anxiety. Methods: Five children aged 8–12 years and their caregivers were recruited through pediatricians. Eligibility was assessed using the MASC-2 and a psychiatrist interview. Each child completed a supervised session with the WebApp, which delivers CBT modules combining psychoeducation, cognitive restructuring, relaxation, and gamified activities. Usability was evaluated using the ita-MAUQ, observation, and interviews. Results: All participants completed the session without dropouts. Mean ita-MAUQ scores were consistently above the midpoint, with the highest ratings for interface design and satisfaction. Children appreciated the interactive, game-like features, while caregivers valued the clarity and practicality of content. Qualitative feedback indicated good comprehensibility and engagement, with suggestions for improving navigation flow and language adaptation. No adverse events occurred. Conclusions: This pilot study supports the feasibility, safety, and acceptability of the new iCBT platform and provides essential insights for its refinement and future large-scale clinical trials.